2022
DOI: 10.1002/adfm.202211140
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Optimization on Pyran‐Fused Nonfullerene Acceptor Enables Organic Solar Cells With an Efficiency Approaching 16% and Reduced Energy Loss

Abstract: Atomic replacement on platforms of nonfullerene acceptor (NFA) with already excellent performance is expected to further optimize the energy levels, absorptions, and even charge transfer dynamics of NFAs effectively without greatly destroying their superior molecular conformations. On the basis of high‐performance F‐series NFAs, the structural optimization at atomic level is performed by replacing sulfur atoms in FO‐2Cl with selenium atoms, thus affording a new NFA labeled as FOSe‐2Cl. FOSe‐2Cl not only inheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…The higher LUMO level of BZ4F-EH and BZ4F-OEH would be favorable for achieving a higher open-circuit voltage (V OC ) in OSC devices. [24,35,48] The optical and CV data of these materials are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher LUMO level of BZ4F-EH and BZ4F-OEH would be favorable for achieving a higher open-circuit voltage (V OC ) in OSC devices. [24,35,48] The optical and CV data of these materials are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…[ 16‐18 ] These two pairs of different side chains are connected to the sp 2 ‐hybridized atoms of the electron‐ deficient‐core, and they extend the plane of the fused central backbone when introducing aromatic groups or heteroatom functionalized side chains, which may have a positive impact on the planarity of the molecule [ 17,19‐20 ] and intramolecular charge transfer. [ 15,21‐33 ] Side chains engineering via tuning of the inner alkyl chain branching point of the A‐DA′D‐A type SMAs has been proven to improve the electronic and morphological properties. [ 34‐35 ] Compared with the inner side chains, the modification of the outer side chains has attracted increasing attention due to their ability to regulate their charge transport/recombination, energetic disorder and voltage losses in the devices.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…It has been reported that the Urbach energy (E U ) is described as the width of the tail of the electronic density of states (DOS) for active layers and reflects the degree of overall energy disorder. [61,62] Thus, the analysis of E U for different active layers was carried out by fitting the spectra of Fourier-transform Adv. Energy Mater.…”
Section: Exciton and Carrier Dynamicsmentioning
confidence: 99%
“…18 Therefore, it is of significance to design and synthesize appealing heteroarenes for constructing novel NFAs toward high-performance OSCs. 19–22…”
Section: Introductionmentioning
confidence: 99%
“…18 Therefore, it is of signicance to design and synthesize appealing heteroarenes for constructing novel NFAs toward high-performance OSCs. [19][20][21][22] BN-heteroarenes, which employ both boron and nitrogen in aromatic hydrocarbons, display unique electronic properties compared with their all-carbon analogues and have shown great potential for applications in organic electronics. 23 Boron and nitrogen atoms can form a B)N coordinate bond or a B-N covalent bond (Fig.…”
Section: Introductionmentioning
confidence: 99%